Maize shelling: A golden opportunity in the battle to improve livelihoods and food security [Tanzania] - Joel, Irene (Technical Centre for Agricultural and Rural Cooperation, 2018)
The national network of small-scale farmers groups in Tanzania, MVIWATA, has partnered with researchers from Germany and Tanzania to promote machine maize shelling in groups, in two villages in the country. Group management training has been provided to the groups in order to help them run their maize processing units as business.